Circulating Carboxylated Osteocalcin Correlates With Skeletal Muscle Mass and Risk of Fall in Postmenopausal Osteoporotic Women - Vitale, Jacopo Antonino; Sansoni, Veronica; Faraldi, Martina; Messina, Carmelo; Verdelli, Chiara; Lombardi, Giovanni; Corbetta, Sabrina (Frontiers in Endocrinology, 2021)
Background Bone and skeletal muscle represent a single functional unit. We cross-sectionally investigated body composition, risk of fall and circulating osteocalcin (OC) isoforms in osteoporotic postmenopausal women to test the hypothesis of an involvement of OC in the bone-muscle crosstalk. Materials and methods Twenty-nine non-diabetic, non-obese, postmenopausal osteoporotic women (age 72.4±6.8 years; BMI 23.0±3.3 kg/m2) underwent to: 1) fasting blood sampling for biochemical and hormone assays, including carboxylated (cOC) and uncarboxylated (uOC) osteocalcin; 2) whole-body dual energy X-ray absorptiometry (DXA) to assess total and regional body composition; 3) magnetic resonance imaging to determine cross-sectional muscle area (CSA) and intermuscular adipose tissue (IMAT) of thigh muscles; 4) risk of fall assessment through the OAK system. Results Appendicular skeletal muscle index (ASMMI) was low in 45% of patients. Forty percent got a low OAK score, consistent with moderate-severe risk of fall, which was predicted by low legs lean mass and increased total fat mass. Circulating cOC levels showed significantly correlated with βCTx-I, lean mass parameters including IMAT, and OAK score. Fractured and unfractured women did not differ for any of the analyzed parameters, though cOC and uOC positively correlated with legs lean mass, OAK score and bone markers only in fractured women. Conclusions Data supported the relationship between OC and skeletal muscle mass and function in postmenopausal osteoporotic women. Serum cOC, but not uOC, emerges as mediator in the bone-muscle crosstalk. Circulating cOC and uOC levels may be differentially regulated in fractured and unfractured osteoporotic women, suggesting underlying differences in bone metabolism.